Effects of Edible bird's nest on quality of Arabian stallion semen and post-breeding induced endometritis in mares - Al-Khaldi, Khalid Obaid Salim (2022)
Despite the remarkable anti-inflammatory and anti-oxidative properties of Edible bird’s nest (EBN), the effects of hydrolysed EBN in stallion semen preservation, post-breeding induced endometritis (PBIE) and fertility of mares remains unknown. This study investigated the effects of 1) different low-dose concentrations of EBN supplementation into EquiPlus® and E-Z Mixin® extenders on the quality of chilled Arabian stallion semen, 2) high doses of EBN added into EquiPlus® and INRA® extenders on the quality of chilled and post-thaw cryopreserved spermatozoa, and 3) intra-uterine hydrolysed EBN (H-EBN) on vital parameters, its immuno-modulatory and anti-oxidative properties, and effects on conception rates in mares with PBIE. Eleven Arabian stallions and 25 mares were used for the three experiments reported in this thesis. In the first experiment, each ejaculate was divided into two groups and diluted into four parts using two extenders (E-Z mixin® and EquiPlus®) and grouped as 0% (control), 0.12%, 0.24% and 0.24% of EBN + seminal plasma (SP). The semen samples were cooled and stored at 5 °C and examined at 0, 24 and 48 h. In the second experiment, ejaculates were divided into two parts for chilling and freezing investigation. In test one, the ejaculates were divided into two equal parts and diluted using EquiPlus® and INRA96® containing 0% (control), 0.12% and 0.24% of EBN. The semen samples were cooled and stored at 5°C and examined at 0, 24 and 48 h. For the freezing evaluation, the ejaculates were divided into two equal parts and diluted using EquiPlus Freeze® and INRA Freeze® containing high doses of EBN (2.4% and 4.8%) and control (0% EBN). The frozen semen was thawed after 7 days at 37ºC for 30 seconds. Sperm kinetic parameters and viability were assessed using computer-assisted sperm analysis (CASA) and Hoechst33342/PI stain, respectively. E-Z mixin® treated semen had significantly higher TM, PM, average path velocity (VAP), straight-line velocity (VSL) and curvilinear velocity (VCL) compared to EquiPlus® at either 24 and/or 48 h. The percentage of viable spermatozoa was significantly higher in E-Z mixin® than EquiPlus® at 0 and 48 h in the control and 0.12% EBN samples. In the third experiment, four mares received an intrauterine infusion of high dose hydrolysed EBN re-suspended in 10.5 mL Ringer’s Lactate (RL), and their vital parameters and endometrial quality were assessed before and after infusion. The remaining 21 mares were controlled for ovulation induction and artificial insemination (AI), and divided into three treatment groups; 10.5 mL of RL (control), high-dose (HEBN) and low-dose hydrolysed EBN (L-EBN) in 10.5 mL of RL. All mares were evaluated using ultrasound for fluid retention 24 h post H-EBN infusion and conception rates on days 14 and 45. Histopathology of endometrial biopsy and analyses of inflammatory indicators were performed. H-EBN had no significant adverse effect on vital signs and endometrial quality. Meanwhile, H-EBN infusion significantly reduced the population of neutrophils from moderate inflammation to normal levels and elevated luminal epithelial height compared to L-EBN and control. Glandular density and conception rate was also higher (P>0.05) in mares treated with H-EBN relative to LEBN and control. These findings depict the promising role of EBN in preserving chilled and frozen semen quality, and as an alternative reproductive medicine in selectively targeting mares susceptible to PBIE.